1998
DOI: 10.1063/1.120680
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced fragmentation of multiwall carbon nanotubes in a polymer matrix

Abstract: We report the observation of single nanotube fragmentation, under tensile stresses, using nanotube-containing thin polymeric films. Similar fragmentation tests with single fibers instead of nanotubes are routinely performed to study the fiber-matrix stress transfer ability in fiber composite materials, and thus the efficiency and quality of composite interfaces. The multiwall nanotube-matrix stress transfer efficiency is estimated to be at least one order of magnitude larger than in conventional fiber-based co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
417
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(446 citation statements)
references
References 23 publications
13
417
2
Order By: Relevance
“…Carbon nanotubes (CNTs) with high structural aspect ratio, excellent mechanical properties and superior electrical conductivity have led to interest in mass production techniques [1][2][3][4]. With CNTs having become commercially available in recent years, more effort from both academic and industrial communities has been put toward their applications.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) with high structural aspect ratio, excellent mechanical properties and superior electrical conductivity have led to interest in mass production techniques [1][2][3][4]. With CNTs having become commercially available in recent years, more effort from both academic and industrial communities has been put toward their applications.…”
Section: Introductionmentioning
confidence: 99%
“…The nanotubes, however, interact with the polymer via weak van der Waals 6 interactions so there is no decrease in stability in the composite. Introduction of nanotubes into the polymer also increases its strength, 8 thermal conductivity, 9 and optical stability. 10 As a hard, conductive plastic this composite shows great potential as an antistatic coating or as electromagnetic shielding for electronic devices.…”
mentioning
confidence: 99%
“…Wagner et al 23 studied the stress transfer between CNTs and a polymer matrix, and showed that CNT-polymer adhesion is quite strong, and that not only the normal stress but also the shear stress transfers from the CNT to the polymer matrix. Thus, for the infinitesimal buckling analysis, we assume that the relation between the pressure and the deflection of the outermost tube surface can be described by the Pasternak foundation model, 21 i.e.,…”
Section: The Elastic Triple-walled Shell Modelmentioning
confidence: 99%